2006
DOI: 10.1002/uog.3809
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester ultrasound and biochemical markers of aneuploidy and the prediction of impending fetal death

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
2
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 33 publications
5
72
2
8
Order By: Relevance
“…The normal pregnancy group comprised of 47 770 pregnancies and the characteristics of this group have been previously described (Spencer et al, 2006a). We identified 222 cases with pre-eclampsia and the characteristics of the cases are described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The normal pregnancy group comprised of 47 770 pregnancies and the characteristics of this group have been previously described (Spencer et al, 2006a). We identified 222 cases with pre-eclampsia and the characteristics of the cases are described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…There is a modest increase in LR with decreasing levels of PAPP-A and in the presence of a normal karyotype such low levels, in addition to being an indicator of increased risk for preeclampsia, also indicated increased risk for other adverse pregnancy outcomes (Spencer et al, 2006a(Spencer et al, , 2007a. The presentation of data in terms of LR curves at any level of PAPP-A MoM is likely to be a more useful aid to counselling than the point estimates from previous studies Smith et al, 2002;Yaron et al, 2002;Dugoff et al, 2004;Spencer et al, 2005b), which are summarised in Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar increase in screening performance can be achieved by examining the additional ultrasound markers in all cases, as well as by a contingency procedure in which the fi rst-stage combined screening categorises the patients into high-, intermediate-, and low-risk categories. In such a case, the new markers are only assessed in the intermediate-risk group in order to stratify the women into either low-or high-risk (1,2,37) .…”
Section: First Trimester Screening Testsmentioning
confidence: 99%
“…13 Low concentrations of PAPP-A have also associated with poor obstetric outcomes such as low birth weight, pre-term delivery, spontaneous foetal loss, small for gestational age and pre-eclampsia. 7,[14][15][16][17] Few studies have looked at biochemical screening markers in instances of confirmed GDM. One study, of a small number of cases, 7 showed a significant reduction in both concentrations of PAPP-A and free hCG, whilst other studies 12,18 found either no significant effect or found a significant reduction only for PAPP-A.…”
Section: Introductionmentioning
confidence: 99%